The Perceived Well-being and Health Costs of Exiting Self-Employment - Milena Nikolova; Boris Nikolaev; Olga Popova (Global Labor Organization (GLO), 2020)
We explore how involuntary and voluntary exits from self-employment affect life and health satisfaction. To that end, we use rich longitudinal data from the German Socio-Economic Panel from 1985 to 2017 and a difference-in-differences estimation. Our findings suggest that while transitioning from self-employment to salaried employment (i.e., a voluntary self-employment exit) brings small improvements in health and life satisfaction, the negative psychological costs of business failure (i.e., switching from self-employment to unemployment) are substantial and exceed the costs of involuntarily losing a salaried job (i.e., switching from salaried employment to unemployment). Meanwhile, leaving self-employment has no consequences for selfreported physical health and behaviors such as smoking and drinking, implying that the costs of losing self-employment are largely psychological. Moreover, former business owners fail to adapt to an involuntary self-employment exit even two or more years after this traumatic event. Our findings imply that policies encouraging entrepreneurship should also carefully consider the costs of business failure.
Keywords: E24; I10; I31; J28; L26; 330; entrepreneurship; self-employment; health; well-being; unemployment; job switches